The Effect of Empowerment, Work Environment, and Career Development on Employees Performance with Work Motivation as The Intervening Variable in The Government of Aceh - Indonesia - Em Yusuf Iis; Wahyuddin; Armanu Thoyib (Quantitative Economics and Management Studies, 2021)
This study aimed to examine the effect of employee empowerment, work environment, and career development on the performance of Aceh Government employees. Data were obtained by distributing questionnaires to 150 employees. Data analysis method was Structural Equation Modeling (SEM). The results showed that employee empowerment, work environment, and employee career development affected work motivation and employee performance significantly. In addition, employee empowerment and work motivation have a direct and significant influence on employee performance, and career development and work environment also have a direct effect on performance. Work motivation partially mediates the influence of employee empowerment, work environment, career development on performance. The Government of Aceh is expected to improve career development in order to create a conducive work environment to improve the performance of Aceh Government employees.